Evolution of duodenal peptic ulcer treatment - Ibrain Rodriguez Rodriguez; Yoan Gabriel Rodríguez Martínez; Ana Ivonne Martínez Portuondo (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Surgical treatment of duodenal peptic ulcer has notably decreased as a consequence of the development of medical treatment. Objective: The objective of this study is to describe the advances in the treatment of duodenal peptic ulcer. Material and Methods: A descriptive study was conducted from the end of the 19th century to the present. The historical-logical method and a deductive-inductive analysis of multiple bibliographic sources were used. Development: Despite ulcer has been recognized as a clinical entity since ancient times, surgeons considered that it is caused by acid; therefore, all efforts were concentrated on removing the acid through an operation. From 1881 on, complications began to be treated. In the decade of the 30s of the last century, complications and the disease were treated. Since 1940, the digestive function has also been preserved and the three basic forms of vagotomy appeared. In the 1970s, novel surgical techniques such as endoscopy, interventional radiology, and minimally invasive surgery were developed. However, powerful acid suppressants as well as the discovery of Helicobacter pylori were taken into consideration for medical treatment.  Once again, surgery was relegated to the treatment of refractory ulcers and complicated ulcers. Conclusions: Medical treatment with anti-Helicobacter therapy associated with potent inhibitors of gastric acid secretion has managed its healing; however, surgery still plays an important role in the treatment of refractory or complicated ulcer.